LACTOSE INTOLERANCE IN CHILDREN AND ADULTS - Pavlović, Momčilo (Medicinski časopis, 2021)
Lactose is the disaccharide found in milk and dairy products. Children and adults with lactose intolerance are unable to tolerate significant amounts of lactose because of an inadequate amount of the enzyme lactase. The condition occurs in three main types: primary, secondary, and primary adult-type hypolactasia. The use of milk in the diet of these individuals may lead to appearance of the irritable bowel syndrome. In persons with lactose intolerance symptoms include diarrhoea, is dominated by abdominal colic, loud peristaltic sounds, increased flatulence and meteorism. A diagnosis of lactose intolerance can usually be made with a careful history, elimination of lactose from the diet, lactose tolerance test, hydrogen breath test and genetic testing. In the absence of appropriate tests in patients with suspected primary adult-type hypolactasia, diagnosis can be made like in patients with food allergy. Treatment is based on the restriction of lactose intake with use of fermented milk products. However, especially for children, if milk and dairy products are eliminated from the diet, it is important to ensure D vitamin and calcium supplementation.
Keywords: lactose intolerance; lactose malapsorption; adult-type lactose intolerance; irritable bowel syndrome